„Idź i pracuj w mojej winnicy” (Mt 21,28). Praca w przypowieściach Ewangelii synoptycznych - Podeszwa, Paweł (Verbum Vitae, 2014)
Parables occupy a significant place in Jesus’ prophesizing and teachings about the Kingdom of God. One of their characteristic traits, as a literary genre, are references to Jesus’ and His listeners’ daily lives. The article presents the analysis of the synoptic parables focused on human work. The material has been divided into two major parts. The first one analyzes the occupations referred to in the parables and the type of work they involve. The second one reflects on the elements of labor law, in particular the employment contracts and related remuneration. The analyzed parables constitute a unique kaleidoscope of occupations existing in the society of the time. Among them, of particular prominence are those connected with land cultivation and farming, such as farmer, sower, harvester, gardener, vineyard keeper and shepherd. Moreover, Jesus’ parables include other occupations such as fisherman, manager, judge, merchant, and banker. Jesus also refers to jobs and tasks such as : guarding and opening the doors (doorkeeper), preparing a feast, waiting tables, taking care of the house, making bread dough, tower building, playing dance music at weddings, wailing and lamenting at funerals. Drawing on Jesus’ parables, one can also notice a wide range of different categories of people who performed particular jobs and tasks. A reference is made to a field owner, vineyard owner, house owner, manager who on behalf of the host administers goods, lease holders, hired and seasonal workers and servants (slaves). The parables also show us the ways of providing reward for work. Servants often performed their duties in exchange for accommodation and food; lease holders in exchange for profit sharing, whereas hired and seasonal workers in exchange for a fixed remuneration. Should the Bible be seen as a specific album presenting photographs of working people, then Jesus’ parables are undoubtedly of particular interest.